2024
DOI: 10.3390/pharmaceutics16020180
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Quality of Nanodrugs According to Their New Property—Radiothermal Emission

Gleb V. Petrov,
Daria A. Galkina,
Alena M. Koldina
et al.

Abstract: Previous studies have shown that complexly shaped nanoparticles (NPs) have their intrinsic radiothermal emission in the millimeter range. This article presents a method for controlling the quality of nanodrugs—immunobiological preparations (IBPs)—based on the detection of their intrinsic radiothermal emissions. The emissivity of interferon (IFN) medicals, determined without opening the primary package, is as follows (µW/m2): IFN-α2b—80 ± 9 (105 IU per package), IFN-β1a—40 ± 5 (24 × 106 IU per package), IFN-γ—3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…In a recent study, we showed that biologically active nanoparticles of irregular shape are capable of radio emission in the millimeter band 14 . The flux density of this emission depends on the temperature, structural features of nanoparticles, their nativeness, and their concentration, which makes it possible to use this method for chemical-analytical control of infusions of medicinal plants and vaccines 27 .…”
Section: Rapid Viability Test For Powdered Substancesmentioning
confidence: 99%
“…In a recent study, we showed that biologically active nanoparticles of irregular shape are capable of radio emission in the millimeter band 14 . The flux density of this emission depends on the temperature, structural features of nanoparticles, their nativeness, and their concentration, which makes it possible to use this method for chemical-analytical control of infusions of medicinal plants and vaccines 27 .…”
Section: Rapid Viability Test For Powdered Substancesmentioning
confidence: 99%